Genomic analyses of Asian honeybee from the Sansha Island in the South China Sea, suggest it’s evolutional origin and environmental adaption - Gao, Jinglin; Tang, Xiangyou; Zhao, Shan; Tao, Kunlin; Shi, Xinyan; Song, Huali; Yao, Yuxin; Jiang, Yan; Wang, Tianbin; Li, Xiang; Zhao, Dongxiang; Xu, Jinshan (Frontiers in Bee Science, 2023)
Discovering new resources and enhancing our knowledge of distribution are crucial for the preservation and utilization of honeybee genetic resources. Our research focused on morphological and population genetic analysis, which revealed significant differences in the SanshaId group compared to others. Notably, the SanshaId group displayed smaller tongue length, averaging at 3.83 mm, and a larger fixation index, indicating a distinct level of subspecies differentiation (Fst = 0.2669). We therefore assumed that A. cerana sanshasis is a new ecotype and subspecies of A. cerana. Estimates of population history indicated that SanshaId population is most closely related to HainanId population, which differed from SanshaId population by about 0.57 Ma due to geological movements. We identified 131 high-frequency non-synonymous mutant genes in the SanshaId group compared to HainanId group. Among these genes, Cuticular genes related to tongue morphology were subject to evolutionary selection, and some genes related to glucose metabolism were highly expressed in the gut. Our results expand the understanding of the distribution range of Asian honeybee and provide a basis for understanding the population dynamics and evolutionary adaptation of A. cerana sanshasis in tropical island environments.